Comparing the range of μ and β angles in 6-17-year-old children of Isfahan with normal occlusion - Saeed Sadeghian; Maryam Hajiahmadi; Ladan Khorrami; Hadi Moshkelgosha (Wolters Kluwer Medknow Publications, 2014)
Background: Linear and angular measurements such as A point, nasion, B point (ANB) angle and Wits appraisal index are not accurate enough to evaluate sagittal relationship of the jaws. The aim of this study was to evaluate and compare the range of μ and β angles in 6-17-year-old children of Isfahan, having normal occlusion. Materials and Methods: This was an analytical descriptive study. For this study, 235 cephalometric radiographs of patients who didn't receive orthodontics treatments and based on 13 indexes had normal occlusion, were selected. After tracing of cephalograms, ANB angle, Wits appraisal index, μ angle (resulted from the intersection of AB line and perpendicular line from point A to mandibular plane) and β angle (resulted from the intersection of AB line and perpendicular line from point A on CB line) were measured. Data was analyzed by t-test, ANOVA and Pierson-Spearman correlation coefficient (P < 0.05). Results: Mean value of μ and β angles were 17.34 ± 3.47 and 31.7 ± 3.31 and ranged from 8-27 to 21.5-39 respectively. According to t-test, there was a significant difference between two sex groups for μ angle (P = 0.02); however, it was not significant for β angle. According to Spearman correlation coefficient, there was no significant difference between age and μ angle; however, β angle was directly and significantly related to age (r = 0.435). There was significant and reverse relationship between μ and β angles with ANB angle and Wits appraisal index. Conclusion: μ and β angles are reliable and can be used to evaluate the anterior-posterior relationship of the jaws.